Heterojunction perovskite tandem battery and method for preparing perovskite tandem battery
By adopting a wet-dry-drying process on crystalline silicon base batteries with high roughness, a high-quality perovskite film is formed, which solves the problems of low coverage, discontinuity and poor uniformity of perovskite films, and improves the performance of perovskite crystalline silicon stacked batteries.
Patent Information
- Application Number
- CN202411866836.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-04-01
AI Technical Summary
It is difficult to form high-quality, continuous and uniform perovskite films on crystalline silicon base batteries with high roughness, resulting in low film coverage, discontinuity, poor uniformity and low crystallization quality.
Using a wet and dry process, the initial functional film layer and metal halide film are first formed on the front of the crystalline silicon base battery, and then the organic ammonium salt solution is spin-coated on the surface of the metal halide film to form an initial perovskite light-absorbing layer, and a high-quality perovskite stacked battery is formed through annealing treatment and the stacking of multi-layer functional film layers.
The coverage, uniformity and crystallization quality of perovskite film are improved, the performance of perovskite crystalline silicon stacked batteries is enhanced, and the photoelectric conversion efficiency is achieved.
Smart Images

Figure CN119744065A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of solar cells, and in particular to a heterojunction perovskite tandem solar cell and a method for preparing the perovskite tandem cell. Background Art
[0002] Since perovskite solar cells have high photoelectric conversion efficiency, combining crystalline silicon cells and perovskite cells to make perovskite crystalline silicon tandem solar cells can maximize the absorption spectrum and improve cell efficiency. Therefore, the application prospects of perovskite crystalline silicon tandem cells are very broad.
[0003] However, how to form a perovskite film on a crystalline silicon bottom cell is a major difficulty in preparing perovskite crystalline silicon tandem cells. Currently, the dry-wet combination process (i.e., dry process + wet process) to prepare perovskite film is considered to be the optimal solution for realizing perovskite tandem cells.
[0004] In order to ensure sufficient light transmittance without sacrificing conversion efficiency, the perovskite film needs to achieve high-quality crystallization at a perovskite thickness of about 1 micron. However, the velvet pyramids of crystalline silicon bottom cells are relatively rough (3-5 microns). The current dry-wet combined process makes it difficult to form micron-level perovskite films on the rough velvet structure, resulting in low film coverage, discontinuity, poor uniformity, and low crystallization quality of the perovskite film on the crystalline silicon bottom cell.
[0005] Therefore, how to optimize the dry-wet combined process preparation method, improve the quality and uniformity of the perovskite film formed on the velvet surface, and achieve continuous, uniform, high-quality crystal growth of the perovskite film with high coverage, so as to prepare perovskite crystalline silicon stacked cells with better performance is a problem that needs to be solved in this field. Summary of the invention
[0006] The present invention aims to solve one of the technical problems in the related art to a certain extent. To this end, the present invention provides a method for preparing a perovskite tandem battery and a heterojunction perovskite tandem battery.
[0007] In order to achieve the above object, as a first aspect of the present invention, a method for preparing a perovskite stacked cell is disclosed, comprising:
[0008] Providing a crystalline silicon bottom cell, the crystalline silicon bottom cell comprising a front side and a back side opposite to each other;
[0009] Sequentially stacking an initial functional film layer and a metal halide film on the front side of the crystalline silicon bottom cell;
[0010] Spin-coating an organic ammonium salt solution on the surface of the metal halide film to form an initial perovskite light-absorbing layer, wherein the solute of the organic ammonium salt solution includes an organic ammonium salt, and the solvent includes a first solvent and a second solvent in a set ratio, and the polarity of the second solvent is greater than that of the first solvent, so that at least a portion of the metal halide film is dissolved in the second solvent to form metal halide particles, and the metal halide particles react with the organic ammonium salt solution to form perovskite microcrystalline particles;
[0011] Annealing the initial perovskite light absorbing layer to obtain a perovskite light absorbing layer;
[0012] A plurality of functional film layers are stacked on the perovskite light-absorbing layer to prepare the perovskite stacked cell.
[0013] Furthermore, the first solvent and the second solvent are organic solvents, and the carbon chain length of the first solvent is greater than the carbon chain length of the second solvent.
[0014] Furthermore, the first solvent includes at least one of isopropanol, propanol and butanol, and the second solvent includes at least one of ethanol, methanol, dimethylformamide and dimethyl sulfoxide.
[0015] Furthermore, in the organic ammonium salt solution, the volume ratio of the solvent is as follows:
[0016] The total volume fraction of the first solvent is between 4 and 10 parts, and the total volume fraction of the second solvent is between 1 and 6 parts.
[0017] Furthermore, sequentially stacking an initial functional film layer and a metal halide film on the front side of the crystalline silicon bottom cell comprises:
[0018] Forming a hole transport layer on the front side of the crystalline silicon bottom cell, wherein the thickness of the hole transport layer is in the range of 10 nm to 30 nm;
[0019] A metal halide film is formed by evaporation deposition on the side of the hole transport layer away from the crystalline silicon bottom cell, wherein the evaporation source includes PbI2, and the evaporation source also includes at least one of PbBr2, CsI and CsBr, and the thickness of the metal halide film is in the range of 300nm to 500nm.
[0020] Furthermore, in the step of spin coating an organic ammonium salt solution on the surface of the metal halide film to form an initial perovskite light-absorbing layer, the spin coating rate is between 1500 rpm and 3000 rpm, the spin coating time is between 15 s and 30 s, the organic ammonium salt includes at least two of formamidine iodide, formamidine bromide, methylammonium iodide and methylammonium chloride, and the total mass concentration of the organic ammonium salt as a solute ranges from 60 mg / mL to 90 mg / mL.
[0021] Furthermore, in the step of annealing the initial perovskite light absorbing layer to obtain the perovskite light absorbing layer, the annealing temperature is in the range of 100° C. to 150° C., and the annealing time is in the range of 10 minutes to 30 minutes.
[0022] Furthermore, stacking a plurality of functional film layers on the perovskite light absorbing layer comprises:
[0023] Forming an electron transport layer by evaporation on the perovskite light absorbing layer, wherein the thickness of the electron transport layer is between 15 nm and 45 nm;
[0024] Forming a second transparent conductive layer on the electron transport layer, wherein the thickness of the second transparent conductive layer is between 60 nm and 120 nm;
[0025] A metal grid line electrode is formed on the second transparent conductive layer, and the thickness of the metal grid line electrode is between 800nm and 1200nm.
[0026] As a second aspect of the present invention, a heterojunction perovskite tandem solar cell is disclosed. The heterojunction perovskite tandem solar cell is prepared by the above-mentioned preparation method. The heterojunction perovskite tandem solar cell includes a crystalline silicon bottom cell, a hole transport layer, a perovskite light absorption layer, an electron transport layer, a second transparent conductive layer, and a metal grid electrode stacked in sequence. The crystalline silicon bottom cell is a heterojunction cell. The heterojunction cell includes a back electrode, a third transparent conductive layer, a first doped silicon layer, an intrinsic layer, a silicon substrate, an intrinsic layer, a second doped silicon layer and a first transparent conductive layer stacked in sequence.
[0027] Furthermore, the velvet roughness of the crystalline silicon bottom cell is between 3 microns and 5 microns, and the thickness of the perovskite light absorption layer is between 0.3um and 1um.
[0028] In the preparation method of the perovskite stacked battery provided by the present invention, the preformed metal halide film has better conformality, can be perfectly covered on the surface velvet structure, and provides a nucleation platform for the subsequent growth of perovskite, further improving the velvet coverage (step coverage ability) of the film of the perovskite film, and better wrapping the lower velvet structure. The first solvent and the second solvent are used as solvents for the organic ammonium salt solution, which can effectively dissolve and disperse the organic ammonium salt solute, increase the solvation effect, and improve the uniformity of the distribution of the organic ammonium salt in the solution. The solution is subsequently spin-coated on the surface of the metal halide film, and the organic ammonium salt can react with the metal halide uniformly at each position to generate a perovskite film, improve the uniform coverage of the film, and make the formed perovskite film higher in quality and less defective. The second solvent has a greater polarity than the first solvent. When the polarity of the second solvent increases, the center of gravity of the positive and negative charges in the molecules does not overlap to a greater extent, resulting in a greater polarity of the molecules, thereby having a stronger electrostatic effect on the solute on the surface of the metal halide film, so that the second solvent can dissolve at least a portion of the positively charged metal ions and metal halide molecules on the surface of the metal halide, so that the metal halide molecules in the metal halide film are slightly soluble in the second solvent to form metal halide solute particles. Further, the metal halide solute particles react chemically with the organic ammonium salt solute in the solution to form perovskite microcrystalline particles in the solution, and the perovskite microcrystalline particles are deposited on the metal halide film and the generated perovskite film, as the nucleation site of the subsequent perovskite, these nucleation points can be evenly dispersed and deposited on the surface through the dispersion of the solution, and the smaller-sized microcrystalline particles are easier to fill the film gaps, improve the film density and coverage, and the larger-sized microcrystalline particles can extend the carrier transport path, reduce the carrier recombination loss, and the microcrystalline particles continue to crystallize and grow, forming a uniform connection with each other, further improving the continuity of the film, and playing a role in controlling the perovskite reaction growth rate in various regions of the surface. Unlike the perovskite film prepared by the conventional dry-wet process, the perovskite microcrystalline particles generated in the present application have a crystalline state, which can make the perovskite that continues to grow on the microcrystalline particles always have a crystalline structure, improve the crystallinity of the perovskite film, and on the other hand, reduce the amorphous content of the perovskite film, and improve the conversion efficiency of the perovskite light-absorbing layer.
[0029] These features and advantages of the present invention will be disclosed in detail in the following specific embodiments and drawings. The best embodiments or means of the present invention will be described in detail in conjunction with the drawings, but they are not intended to limit the technical solutions of the present invention. In addition, there are multiple features, elements, and components that appear in each of the following texts and drawings, and different symbols or numbers are marked for convenience, but they all represent components with the same or similar structures or functions. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] The present invention will be further described below in conjunction with the accompanying drawings:
[0031] Figure 1 It is a flow chart of an implementation method of the method for preparing a solar cell provided by the present invention;
[0032] Figure 2 is a flow chart of another embodiment of the method for preparing a solar cell provided by the present invention;
[0033] Figure 3 It is a structural schematic diagram of an implementation mode of a solar cell provided by the present invention;
[0034] Figure 4 is a schematic structural diagram of another embodiment of a solar cell provided by the present invention;
[0035] Figure 5 is a photovoltaic performance test curve diagram of the solar cell provided by Examples 1 to 4 of the present invention;
[0036] Figure 6 is a scanning electron microscope photograph of the surface of the perovskite light-absorbing layer in the solar cell provided in Example 1 of the present invention;
[0037] Figure 7 This is a scanning electron microscope photograph of the cross section of the solar cell provided in Example 1 of the present invention.
[0038] Description of Reference Numerals
[0039] 1: Perovskite tandem solar cell; 10: Crystalline silicon bottom cell; 11: First transparent conductive layer;
[0040] 12: hole transport layer; 13: perovskite light absorption layer; 14: electron transport layer; 15: buffer layer;
[0041] 16: second transparent conductive layer; 17: metal grid electrode; 18: anti-reflection film
[0042] 21: second doped silicon layer; 22: intrinsic layer; 23: silicon substrate; 24: first doped silicon layer;
[0043] 11b: third transparent conductive layer; 17b: back electrode. DETAILED DESCRIPTION
[0044] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements with the same or similar functions. The embodiments in the implementation manner are intended to be used to explain the present invention and should not be construed as limiting the present invention.
[0045] References to "one embodiment" or "an example" or "an example" in this specification mean that a particular feature, structure, or characteristic described in conjunction with the embodiment itself may be included in at least one embodiment disclosed in the present application. The appearance of the phrase "in one embodiment" in various places in the specification does not necessarily refer to the same embodiment.
[0046] It should be pointed out that in the present invention, “inner side” refers to the side close to the initial substrate, and “outer side” refers to the side away from the initial substrate.
[0047] The inventors of the present application have found that the height difference of the velvet pyramids prepared in the existing crystalline silicon heterojunction cells is generally between 3 microns and 5 microns (roughness). The subsequent preparation of stacked perovskite solar cells also requires thin film deposition at a roughness of 3 microns to 5 microns, and the thickness of the perovskite film is generally between several hundred nanometers and 1 micron. In this case, it is very difficult to achieve high-quality, uniform and continuous growth of the perovskite film, and the film coverage is also difficult to be complete.
[0048] In order to adapt to the roughness of velvet crystalline silicon, under the conditions of 3 to 5 micron velvet pyramids, the complete coverage and growth of perovskite films are achieved. The key to obtaining efficient and stable perovskite / heterojunction silicon is to prepare high-quality perovskite films by combining dry and wet methods. The preparation method first evaporates a layer of lead iodide film on the surface of the velvet crystalline silicon cell. The evaporated lead iodide film can be conformal, perfectly present the shape of the velvet, and evenly cover it. Then, an organic ammonium salt solution is used to react with the lead iodide film to achieve in-situ growth of perovskite films on velvet heterojunction silicon, achieving higher film coverage and higher quality perovskite films. At the same time, it is also required that the prepared perovskite film has more crystalline states.
[0049] In the current existing process, isopropanol is used as a solvent for organic salts because of its unique properties. On the one hand, isopropanol can dissolve most organic ammonium salts well; on the other hand, isopropanol will not destroy the lead iodide skeleton structure at all. Taking advantage of this property, the dry-wet combined process uses a large amount of isopropanol as an organic solvent medium to achieve an in-situ reaction of organic ammonium salts and lead iodide to obtain a perovskite film. However, the in-depth understanding of basic solution chemistry, such as nucleation, crystal growth, precursor coordination molecule interactions, and the chemical pathways for the final formation of perovskite films, cannot keep up with the rapid development of high-performance perovskite solar cells. The isopropanol solvent used is still difficult to achieve continuous, high-quality deposition and growth of perovskite films on a micrometer scale, and it is difficult to obtain a perovskite film with suitable film thickness and excellent crystallization, which in turn affects the efficiency of perovskite and its stacked devices. Therefore, the preparation of 1 micron perovskite on a roughness of 3-5 microns and the control of perovskite crystallization are the key to preparing high-quality perovskite films. In addition, for the liquid phase preparation of perovskite films, the design of the chemical reaction of the precursor solution is crucial because it can control the nucleation and crystal growth, affecting the film morphology and subsequent device performance.
[0050] The present invention optimizes the perovskite preparation process, especially for high-quality perovskite films prepared by dry + wet methods. In addition, the patent of the present invention applies the dry-wet combination process to the preparation of perovskite / heterojunction silicon stacked devices, and the use of the solvent engineering can realize the preparation of efficient perovskite and its stacked devices.
[0051] As a first aspect of the present invention, a method for preparing a solar cell is provided, such as Figure 1 As shown, including:
[0052] In step S100, a crystalline silicon bottom cell is provided, wherein the crystalline silicon bottom cell comprises a front side and a back side opposite to each other;
[0053] In step S110, an initial functional film layer and a metal halide film are sequentially stacked on the front side of the crystalline silicon bottom cell;
[0054] In step S120, an organic ammonium salt solution is applied to the surface of the metal halide film to form an initial perovskite light-absorbing layer, wherein the solute of the organic ammonium salt solution includes an organic ammonium salt, and the solvent includes a first solvent and a second solvent in a set ratio, and the polarity of the second solvent is greater than that of the first solvent, so that at least a portion of the metal halide film is dissolved in the second solvent to form metal halide particles, and the metal halide particles react with the organic ammonium salt solution to form perovskite microcrystalline particles;
[0055] In step S130, the initial perovskite light absorbing layer is annealed to obtain a perovskite light absorbing layer;
[0056] In step S140, a plurality of functional film layers are stacked on the perovskite light absorbing layer to prepare a perovskite solar cell.
[0057] In step S100, the present invention does not specifically limit the structure of the crystalline silicon bottom cell. The preparation method of the present invention can prepare a perovskite stacked solar cell, wherein the perovskite cell can be connected in series with various types of cells as a stacked cell to improve the maximum efficiency. Preferably, the crystalline silicon bottom cell can be selected from one of a PERC cell, a BC cell, an HJT cell or a TOPCon cell. Of course, the present invention is not limited to the crystalline silicon bottom cell exemplified above, and can also be other solar cells, such as copper indium gallium selenide solar cells. In some embodiments, the initial crystalline silicon bottom cell is selected from a crystalline silicon heterojunction cell, and the preparation method of the present invention is used to prepare a cell on the crystalline silicon heterojunction cell, and finally a perovskite-crystalline silicon heterojunction stacked solar cell can be obtained. For another example, only a single-junction perovskite cell can be made.
[0058] In step S110, the present invention does not specifically limit the structure of the initial functional film layer. As an optional implementation, forming the initial functional film layer on the front side of the crystalline silicon bottom cell includes:
[0059] Forming a first transparent conductive film on the front side of the crystalline silicon bottom cell by magnetron sputtering deposition, wherein the thickness of the first transparent conductive film is in the range of 5 nm to 20 nm;
[0060] Forming a hole transport layer on the side of the first transparent conductive film away from the crystalline silicon bottom cell, wherein the thickness of the hole transport layer is in the range of 10 nm to 30 nm;
[0061] In step S110, in the solar cell preparation method provided by the present invention, the pre-formed metal halide film has better conformality, can perfectly cover the surface velvet structure, and provide a nucleation platform for the subsequent growth of perovskite, further improving the velvet coverage (step coverage ability) of the perovskite film, and better wrapping the lower velvet structure. The present invention does not specifically limit how to form the metal halide film. For example, it can be prepared by conventional methods such as chemical vapor deposition, atomic layer deposition, thermal evaporation, and solution spin coating.
[0062] As an optional implementation, a metal halide film is formed by evaporation deposition on the side of the hole transport layer facing away from the crystalline silicon bottom cell, wherein the evaporation source includes PbI2, and the evaporation source also includes at least one of PbBr2, CsI and CsBr, and the thickness of the metal halide film is in the range of 300nm to 500nm. The evaporation source can also be PbX2 (X=at least one of Cl, Br and I).
[0063] In step S120, the present invention does not specifically limit the type of organic ammonium salt. Preferably, the organic ammonium salt includes at least two of formamidine iodide (FAI), formamidine bromide (FABr), methyl ammonium iodide (MAI) and methyl ammonium chloride (MACl). As further preferred, the organic ammonium salt includes FAI, FABr, MAI and MACl, and the organic ammonium salt is between 60mg / mL and 90mg / mL as a solute total mass concentration, wherein the organic ammonium salt components are weighed by mass to meet the following proportion ranges, FAI is between 30mg and 50mg, FABr is between 15mg and 25mg, MAI is between 5mg and 15mg, and MACl is between 5mg and 9mg.
[0064] Perovskite precursors such as lead halide (PbX2) and organic ammonium salts are generally dispersed in the solvent by coordinating with solvent molecules and forming micelles. According to the electron orbital configuration theory, the lone pair of electrons in the 6s orbit of Pb is easy to lose, so lead halide appears as a Lewis acid, while polar aprotic solvents containing elements such as O, S, and N, such as dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), are Lewis bases. Therefore, when lead halide is dissolved in the above solvents, an acid-base reaction occurs to generate solvent compounds PbX2·DMF and PbX2·DMSO. Since the Pb-I bond energy is weaker than that of Pb-Br and Pb-Cl, the coordination between PbI2 and the solvent is stronger than that of PbBr2 and PbCl2. By adjusting the solution concentration, temperature and solvent type, a variety of coordination products such as PbI+, PbI2, PbI3-, and PbI42- can be formed. PbI2 is stacked along the (001) crystal plane to form a layered structure, and the layers are connected by van der Waals forces. When it is dissolved in a solvent, the van der Waals forces between the (001) crystal planes are destroyed, that is, the layered structure of PbI2 is destroyed, PbI2 gradually disintegrates, and complex solution chemical reactions occur, forming various lead iodates (such as PbI3- and PbI42-, etc.).
[0065] In order to better dissolve the organic ammonium cation, preferably, the solvent includes an organic solvent with multiple length carbon chains. Using an organic solvent as the solvent of the organic ammonium salt solution, the organic ammonium salt solute can be effectively dissolved and dispersed, the solvation effect is increased, the distribution uniformity of the organic ammonium salt in the solution is improved, and the solution is subsequently applied to the surface of the metal halide film, and the organic ammonium salt can react with the metal halide uniformly at each position to generate a perovskite film, improve the uniform coverage of the film, and make the perovskite film formed higher in quality, with fewer defects. As further preferred, the first solvent includes at least one of isopropanol, propanol and butanol, and the second solvent includes at least one of ethanol, methanol, dimethylformamide, and dimethyl sulfoxide.
[0066] The ability of a solvent to dissolve cations can be characterized by its polarity value. Organic solvents with high polarity values, such as ethanol, methanol, dimethylformamide, dimethyl sulfoxide, N-methyl-2-pyrrolidone (NMP), dimethylacetamide (DMAC), and dimethylpropylene urea (DMPU), are easy to coordinate with PbX2 to form solvated coordination intermediates. On the contrary, solvents with low polarity values, such as isopropanol, are not easy to coordinate with Pb2+ and cannot dissolve metal halides.
[0067] Based on this, the second solvent has a greater polarity than the first solvent. When the polarity of the second solvent increases, the center of gravity of the positive and negative charges in the molecules does not overlap to a greater extent, resulting in a greater polarity of the molecules, thereby having a stronger electrostatic effect on the solute on the surface of the metal halide film, so that the second solvent can dissolve at least a portion of the positively charged metal ions and metal halide molecules on the surface of the metal halide, so that the metal halide molecules in the metal halide film are slightly soluble in the second solvent to form metal halide solute particles.
[0068] In order to make the second solvent slightly soluble in metal halides, the polarity of the solvent needs to be limited. When the polarity of the solvent is too large, when an organic ammonium salt is added as the second solvent, its solubility in metal halides also increases rapidly. However, for the conformal deposition of metal halide films prepared on velvet silicon, excessive dissolution of the solvent will destroy the effect of conformal deposition, resulting in the inability of the perovskite film of the two-step reaction to completely cover the velvet structure. Preferably, the polarity of the first solvent is in the range of 3 to 4, and the polarity of the second solvent is in the range of 4 to 7.
[0069] Furthermore, the metal halide solute particles react chemically with the organic ammonium salt solute in the solution to form perovskite microcrystalline particles in the solution. The perovskite microcrystalline particles are deposited on the metal halide film and the generated perovskite film, and serve as nucleation sites for subsequent perovskites. These nucleation sites can be evenly dispersed and deposited on the surface through the dispersion of the solution, and the smaller-sized microcrystalline particles are easier to fill the film gaps, thereby improving the film density and coverage, while the larger-sized microcrystalline particles can extend the carrier transport path and reduce the carrier recombination loss. The microcrystalline particles continue to crystallize and grow, forming uniform connections with each other, further improving the continuity of the film and playing a role in controlling the perovskite reaction growth rate in various regions of the surface.
[0070] In some embodiments, in an organic ammonium salt solution, the first solvent includes isopropanol, the second solvent includes at least one of methanol and ethanol, and methanol is added to the organic ammonium salt solution as the most polar solvent, and the solubility of methanol in metal halides also increases rapidly. However, for the conformal deposition metal halide film prepared on velvet silicon, excessive dissolution of the solvent will destroy the effect of conformal deposition, resulting in the inability of the perovskite film of the two-step reaction to completely cover the velvet structure. Therefore, it is necessary to make necessary restrictions on the content or proportion of the second solvent. When a slightly soluble interface formed by a lower dose of polar methanol solution is used, it can promote the growth of the perovskite film and form a conformal deposition of perovskite on velvet crystalline silicon. Preferably, the volume fraction ratio of the first solvent to the second solvent is between 0.6 and 10. Within the above volume fraction ratio range, a relatively ideal slightly soluble effect can be obtained to form perovskite microcrystalline particles that meet the requirements without causing excessive dissolution. As a further preference, in the organic ammonium salt solution, the volume ratio of the solvents is as follows: the total volume fraction of the first solvent is between 4 and 10 parts, and the total volume fraction of the second solvent is between 1 and 6 parts.
[0071] The present invention does not specifically limit the spin coating process parameters, but adopts a variety of organic solvents with different polarities. In order to obtain a better slightly soluble effect, as an optional implementation method, in the step of applying an organic ammonium salt solution to the surface of a metal halide film to form an initial perovskite light-absorbing layer, the spin coating rate is between 1500rpm and 3000rpm, and the spin coating time is between 15s and 30s. According to the increase of the polar solvent methanol, the spin coating time is also appropriately shortened. Specifically, when the precursor solution is obtained by using isopropanol: methanol as a solvent ratio of 8:2, the spin coating time on the homogenizer is reduced to 15s. This is because the amount of the polar solvent (methanol) is increased, which will accelerate the solubility rate of the inorganic salt. By reducing the spin coating time, the excessive dissolution of the inorganic salt can be reduced, thereby forming a slightly soluble interface phase, promoting the crystal growth of the perovskite film, and preferably, the thickness of the formed perovskite film is in the range of 0.3um to 1um.
[0072] In step S130, annealing can affect the crystallization quality of the film, and the regulation of the film crystallization rate plays a decisive role in the formation of microcrystals. Rapid crystallization may lead to uneven distribution of microcrystal particles, thereby affecting the uniformity of the film, while moderately slow crystallization can promote uniform growth, but too slow may introduce amorphous areas and affect the coverage. Rapid volatilization may lead to insufficient crystal growth and the formation of pinholes, while moderate annealing can promote the recrystallization and oriented growth of microcrystals, thereby improving the uniformity and density of the film. Preferably, in the step of annealing the initial perovskite light-absorbing layer to obtain the perovskite light-absorbing layer, preferably, the annealing temperature is in the range of 100°C to 150°C, the annealing time is between 10 minutes and 30 minutes, and the thickness of the formed perovskite light-absorbing layer is in the range of 0.3um to 1um.
[0073] Different from the amorphous perovskite film prepared by conventional dry-wet processes, the perovskite microcrystalline particles generated in the present application are crystalline. On the one hand, it can ensure that the perovskite that continues to grow on the microcrystalline particles always has a crystalline structure. On the other hand, it reduces the amorphous content of the perovskite film and improves the conversion efficiency of the perovskite light-absorbing layer.
[0074] In step S140, as an optional implementation, a multi-layer functional film layer is stacked on the perovskite light absorbing layer to prepare a perovskite solar cell, including:
[0075] An electron transport layer is formed by evaporating on the perovskite light absorbing layer, and the thickness of the electron transport layer is between 15nm and 45nm;
[0076] Forming a second transparent conductive layer on the electron transport layer, wherein the thickness of the second transparent conductive layer is between 60 nm and 120 nm;
[0077] Forming a metal grid line electrode on the second transparent conductive layer, wherein the thickness of the metal grid line electrode is between 800nm and 1200nm;
[0078] An anti-reflection film is formed on the metal grid electrode, and the thickness of the anti-reflection film is between 80nm and 120nm.
[0079] As a specific embodiment of the preparation method of the present invention, Figure 2 shown.
[0080] In step S200, a heterojunction silicon bottom cell is provided, wherein the heterojunction silicon bottom cell comprises a front side and a back side opposite to each other;
[0081] In step S210, a first transparent conductive film is formed on the front surface by magnetron sputtering deposition, and the thickness of the first transparent conductive film is in the range of 5 nm to 20 nm;
[0082] In step S220, a hole transport layer is formed on the first transparent conductive film, and the thickness of the hole transport layer is in the range of 10 nm to 30 nm;
[0083] In step S230, a metal halide film is formed on the hole transport layer by evaporation deposition, wherein the evaporation source includes PbI2, and the evaporation source also includes at least one of PbBr2, CsI and CsBr, and the thickness of the metal halide film is in the range of 300nm to 500nm;
[0084] In step S240, an organic ammonium salt solution is spin-coated on the surface of the metal halide film to form an initial perovskite light-absorbing layer, wherein the solute of the organic ammonium salt solution includes an organic ammonium salt, and the solvent includes methanol, ethanol and isopropanol in a set ratio;
[0085] In step S250, the initial perovskite light absorbing layer is annealed to obtain a perovskite light absorbing layer, the annealing temperature is in the range of 100° C. to 150° C., and the annealing time is between 10 minutes and 30 minutes;
[0086] In step S260, C60 is evaporated on the perovskite light absorption layer to form an electron transport layer, and the thickness of the electron transport layer is between 15 nm and 45 nm;
[0087] In step S270, a second transparent conductive layer is formed on the electron transport layer, and the thickness of the second transparent conductive layer is between 60 nm and 120 nm. Specifically, a tin dioxide buffer layer can be formed between the second transparent conductive layer and the electron transport layer by atomic layer deposition to avoid sputtering damage. The thickness of the buffer layer is between 15 nm and 30 nm. The material of the second transparent conductive layer includes but is not limited to IZO / ITO / AZO, etc.;
[0088] In step S280, a metal grid line electrode is formed on the second transparent conductive layer, wherein the thickness of the metal grid line electrode is between 800 nm and 1200 nm, wherein the metal grid line electrode comprises at least one of silver, copper, aluminum and gold. The present invention does not specifically limit how to form the metal grid line, and the metal grid line electrode can be formed by at least one method of screen printing, ink printing, electrochemical deposition, evaporation, magnetron sputtering, and ion beam evaporation.
[0089] In step S290, an anti-reflection film is formed on the metal gate electrode. The thickness of the anti-reflection film is between 80 nm and 120 nm. The material of the anti-reflection film includes but is not limited to lithium fluoride, magnesium fluoride, and the like.
[0090] As a second aspect of the present invention, a perovskite tandem solar cell is provided. The perovskite tandem solar cell is prepared by the above-mentioned preparation method. Figure 3 and Figure 4As shown. The perovskite tandem solar cell 1 comprises a crystalline silicon bottom cell 10, a hole transport layer 12, a perovskite light absorption layer 13, an electron transport layer 14, a second transparent conductive layer 16, a metal grid electrode 17 and an anti-reflection film 18 stacked in sequence. In order to prevent the transparent conductive film from being damaged by sputtering, a buffer layer 15 is preferably provided between the electron transport layer 14 and the second transparent conductive layer 16. The crystalline silicon bottom cell 10 comprises a back electrode 17b, a third transparent conductive layer 11b, a first doped silicon layer 24, an intrinsic layer 22, a silicon substrate 23, an intrinsic layer 22, a second doped silicon layer 21 and a first transparent conductive layer 11 stacked in sequence.
[0091] The solar cell perovskite light absorption layer film of the present invention has high coverage, continuous and uniform, high-quality crystallization, and the device has higher photoelectric conversion efficiency.
[0092] The present invention will be further explained below in conjunction with the embodiments.
[0093] Example
[0094] Example 1
[0095] Step 1, sequentially preparing a first transparent conductive film and a hole transport layer on an initial substrate, wherein the initial substrate is a crystalline silicon heterojunction battery, the first transparent conductive film comprises an ITO conductive glass having a thickness between 5 nm and 20 nm, the hole transport layer has a thickness between 10 nm and 30 nm, and the hole transport layer is Me-4PACz;
[0096] Step 2, forming a metal halide film on the hole transport layer by evaporation deposition, wherein the evaporation sources are PbI2, PbBr2 and CsI, respectively, and the thickness of the metal halide film is in the range of 300nm to 500nm;
[0097] Step 3, spin coating an organic ammonium salt solution on the surface of the metal halide film to form an initial perovskite light-absorbing layer, wherein the solute of the organic ammonium salt solution includes FAI, FABr, MAI and MACl, the solvent includes isopropanol and ethanol, the volume ratio is 9:1, and the total mass concentration range of the organic ammonium salt as a solute is between 60 mg / mL and 90 mg / mL, wherein the components of the organic ammonium salt are weighed by mass to meet the following requirements: FAI is 40 mg, FABr is 20 mg, MAI is 10 mg, and MACl is 10 mg;
[0098] Step 4, annealing the initial perovskite light absorbing layer to obtain a perovskite light absorbing layer, wherein the annealing temperature is in the range of 100° C. to 150° C., and the annealing time is between 10 minutes and 30 minutes;
[0099] Step 5, vapor-depositing C60 on the perovskite light-absorbing layer as an electron transport layer, wherein the thickness of the electron transport layer is between 15 nm and 45 nm;
[0100] Step 6: forming a tin dioxide buffer layer by atomic layer deposition to avoid sputtering damage, wherein the thickness of the buffer layer is between 15 nm and 30 nm;
[0101] Step 7: forming a second transparent conductive layer by magnetron sputtering, wherein the thickness of the second transparent conductive layer is between 60 nm and 120 nm, and the material of the second transparent conductive layer is ITO;
[0102] Step 8, forming a metal grid line electrode on the second transparent conductive layer, wherein the thickness of the metal grid line electrode is between 800 nm and 1200 nm, and the material of the metal grid line is Ag;
[0103] Step 9: Form an anti-reflection film on the metal grid electrode, wherein the thickness of the anti-reflection film is between 80 nm and 120 nm and the material of the anti-reflection film is MgF 2 , thereby obtaining a solar cell 1 .
[0104] Example 2
[0105] A solar cell was prepared by the same preparation method as in Example 1, except that the solvent included isopropanol and methanol in a volume ratio of 9:1, and a solar cell 2 was prepared.
[0106] Example 3
[0107] A solar cell was prepared by the same preparation method as in Example 1, except that the solvent included isopropanol, ethanol and methanol in a volume ratio of 8:1:1, and a solar cell 3 was prepared.
[0108] Example 4
[0109] A solar cell was prepared by the same preparation method as in Example 1, except that the solvent included isopropanol, ethanol and methanol in a volume ratio of 7:2:1, and a solar cell 4 was prepared.
[0110] Test Case
[0111] The perovskite light absorbing layer and the cross section of the solar cell of Example 1 of the present invention were tested by scanning electron microscope, and the following results were obtained: Figure 6 and Figure 7 The microstructure photo shown. Example 1 uses alcohol organic solvents of different polarities to participate in the crystallization reaction process of perovskite. The metal halide is slightly dissolved in ethanol with higher polarity. Perovskite microcrystalline particles are obtained in the early stage of dry-wet reaction, and participate in the formation reaction of perovskite crystals. Finally, a perovskite film with uniform texture and excellent crystallization is obtained. The upper surface morphology of the perovskite film in Example 1 is as follows Figure 6 As shown, dense and smooth perovskite grains can be observed; Figure 7 The cross section shown also shows a clear layer boundary structure.
[0112] The specific structure of the solar cell provided in Examples 1 to 4 of the present invention is as follows Figure 4 shown.
[0113] The photovoltaic performance of the solar cells prepared in Examples 1 to 4 was tested using a solar cell testing system to obtain a current-voltage (JV) curve, as shown in FIG. Figure 5 As shown. Table 1 records the photoelectric performance parameters of Examples 1 to 4 extracted from the JV curve. In Examples 1 to 4 of the present invention, a perovskite film is deposited on heterojunction silicon to obtain a heterojunction silicon / perovskite tandem solar cell, which can combine the advantages of the top cell and the bottom cell to obtain an efficient tandem perovskite solar cell, wherein, in Example 1 and Example 2, after ethanol or methanol is added to the solvent, perovskite microcrystalline particles can be formed when preparing the perovskite light-absorbing layer, on the one hand, the perovskite film has a higher crystallinity and better quality, and on the other hand, the perovskite microcrystalline particles make the formed light-absorbing layer film more continuous and uniform, so compared with conventional perovskite tandem cells, the filling factor, open circuit voltage and current density of the tandem cell of the present invention are significantly improved (the open circuit voltage Voc of conventional perovskite tandem cells is less than 1.8V, the filling factor FF is generally about 70%, and the short-circuit current density is about 20mA / cm2), which also promotes the improvement of device efficiency (the efficiency of conventional perovskite tandem cells is generally only between 20% and 26%). However, in Examples 3 and 4, the addition of excessive ethanol or methanol causes it to excessively dissolve the metal halide film, thereby destroying the effect of conformal deposition and reducing the continuous and uniform deposition and crystallization quality of the perovskite, resulting in a decrease in device efficiency compared to Examples 1 and 2. However, compared with conventional perovskite stacked cells, their open circuit voltage Voc, fill factor FF, short circuit current density and energy conversion efficiency PCE are still improved.
[0114] Table 1
[0115] <![CDATA[V OC (V)]]> <![CDATA[J SC (mA / cm 2 )]]> FF(%) PCE(%) Example 1 1.83 21.1 75% 28.9% Example 2 1.83 21.1 74.5% 28.8% Example 3 1.82 21.0 73% 27.9% Example 4 1.81 21.1 70% 26.7% Conventional laminated battery 1.8 20 70% 26%
[0116] The above are only specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that the present invention includes but is not limited to the contents described in the drawings and the above specific embodiments. Any modification that does not deviate from the functional and structural principles of the present invention will be included in the scope of the claims.
Claims
1. A method for preparing a perovskite tandem battery, characterized in that: include: Providing a crystalline silicon bottom cell, the crystalline silicon bottom cell comprising a front side and a back side opposite to each other; Sequentially stacking an initial functional film layer and a metal halide film on the front side of the crystalline silicon bottom cell; Spin-coating an organic ammonium salt solution on the surface of the metal halide film to form an initial perovskite light-absorbing layer, wherein the solute of the organic ammonium salt solution includes an organic ammonium salt, and the solvent includes a first solvent and a second solvent in a set ratio, and the polarity of the second solvent is greater than that of the first solvent, so that at least a portion of the metal halide film is dissolved in the second solvent to form metal halide particles, and the metal halide particles react with the organic ammonium salt solution to form perovskite microcrystalline particles; Annealing the initial perovskite light absorbing layer to obtain a perovskite light absorbing layer; A plurality of functional film layers are stacked on the perovskite light-absorbing layer to prepare the perovskite stacked cell.
2. The preparation method according to claim 1, characterized in that: The first solvent and the second solvent are organic solvents, and the carbon chain length of the first solvent is greater than the carbon chain length of the second solvent.
3. The preparation method according to claim 2, characterized in that: The first solvent includes at least one of isopropanol, propanol and butanol, and the second solvent includes at least one of ethanol, methanol, dimethylformamide and dimethyl sulfoxide.
4. The preparation method according to claim 1, characterized in that: In the organic ammonium salt solution, the volume ratio of the solvent is as follows: The total volume fraction of the first solvent is between 4 and 10 parts, and the total volume fraction of the second solvent is between 1 and 6 parts.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The initial functional film layer and the metal halide film are sequentially stacked on the front side of the crystalline silicon bottom cell, comprising: Forming a hole transport layer on the front side of the crystalline silicon bottom cell, wherein the thickness of the hole transport layer is in the range of 10 nm to 30 nm; A metal halide film is formed by evaporation deposition on the side of the hole transport layer away from the crystalline silicon bottom cell, wherein the evaporation source includes PbI2, and the evaporation source also includes at least one of PbBr2, CsI and CsBr, and the thickness of the metal halide film is in the range of 300nm to 500nm.
6. The preparation method according to any one of claims 1 to 4, characterized in that: In the step of spin coating an organic ammonium salt solution on the surface of the metal halide film to form an initial perovskite light-absorbing layer, the spin coating rate is between 1500 rpm and 3000 rpm, the spin coating time is between 15 s and 30 s, the organic ammonium salt includes at least two of formamidine iodide, formamidine bromide, methylammonium iodide and methylammonium chloride, and the total mass concentration of the organic ammonium salt as a solute ranges from 60 mg / mL to 90 mg / mL.
7. The preparation method according to any one of claims 1 to 4, characterized in that: In the step of annealing the initial perovskite light absorbing layer to obtain the perovskite light absorbing layer, the annealing temperature is in the range of 100° C. to 150° C., and the annealing time is in the range of 10 minutes to 30 minutes.
8. The preparation method according to any one of claims 1 to 4, characterized in that: The method of stacking a plurality of functional film layers on the perovskite light absorbing layer comprises: Forming an electron transport layer by evaporation on the perovskite light absorbing layer, wherein the thickness of the electron transport layer is between 15 nm and 45 nm; Forming a second transparent conductive layer on the electron transport layer, wherein the thickness of the second transparent conductive layer is between 60 nm and 120 nm; A metal grid line electrode is formed on the second transparent conductive layer, and the thickness of the metal grid line electrode is between 800nm and 1200nm.
9. A heterojunction perovskite tandem solar cell, characterized in that: The heterojunction perovskite tandem solar cell is prepared by the preparation method described in any one of claims 1 to 8, and the heterojunction perovskite tandem solar cell includes a crystalline silicon bottom cell, a hole transport layer, a perovskite light absorption layer, an electron transport layer, a second transparent conductive layer, and a metal grid electrode stacked in sequence. The crystalline silicon bottom cell is a heterojunction cell, and the heterojunction cell includes a back electrode, a third transparent conductive layer, a first doped silicon layer, an intrinsic layer, a silicon substrate, an intrinsic layer, a second doped silicon layer, and a first transparent conductive layer stacked in sequence.
10. The heterojunction perovskite tandem solar cell according to claim 9, characterized in that: The velvet roughness of the crystalline silicon bottom cell is between 3 microns and 5 microns, and the thickness of the perovskite light absorption layer is between 0.3um and 1um.
Citation Information
Cited By
Laminated cell, preparation method thereof and photovoltaic module
CN120882227A
An all-inorganic silicon-based perovskite solar tandem cell and its preparation method
CN122679810A